Quantification of Tau in Cerebrospinal Fluid by Immunoaffinity Enrichment and Tandem Mass Spectrometry. (1st April 2014) - McAvoy, Thomas; Lassman, Michael E; Spellman, Daniel S; Ke, Zhenlian; Howell, Bonnie J; Wong, Oitak; Zhu, Lan; Tanen, Michael; Struyk, Arie; Laterza, Omar F
Abstract: BACKGROUND: Cerebrospinal fluid (CSF) tau is a common biomarker for Alzheimer disease (AD). Measurements of tau have historically been performed using immunoassays. Given the molecular diversity of tau in CSF, the selectivity of these immunoassays has often been questioned. Therefore, we aimed to develop an analytically sensitive and selective immunoaffinity liquid chromatography–tandem mass spectrometry (LC-MS/MS) (IA-MS) assay. METHODS: IA-MS sample analysis involved the addition of an internal standard, immunoaffinity purification of tau using a tau monoclonal antibody coupled to magnetic beads, trypsin digestion, and quantification of a surrogate tau peptide by LC-MS/MS using a Waters Trizaic nanoTile ultraperformance LC microfluidic device. Further characterization of tau peptides was performed by full-scan MS using a Thermo Orbitrap LC-MS. CSF samples from a cohort of age-matched controls and patients with AD were analyzed by the IA-MS method as well as a commercially available immunoassay. RESULTS: The IA-MS assay had intra- and interassay imprecision values of 3.2% to 8.1% CV and 7.8% to 18.9% C, respectively, a mean recovery of 106%, and a limit of quantification of 0.25 pmol/L and was able to quantify tau concentrations in all human specimens tested. The IA-MS assay showed a correlation of R 2 = 0.950 against a total-tau immunoassay. In patients with AD, tau was increased approximately 2-fold. CONCLUSIONS: Combining immunoaffinity enrichment with microflow LC-MS/MS analysis is an effective approach for the development of a highly selective assay to measure total tau and, potentially, other posttranslationally modified forms of tau in CSF.